Mitochondrial dysfunction and inhibition of myoblast differentiation in mice with high‐fat‐diet‐induced pre‐diabetes. Issue 5 (26th October 2018) - Xu, Dengqiu; Jiang, Zhenzhou; Sun, Zeren; Wang, Lu; Zhao, Guolin; Hassan, Hozeifa M.; Fan, Sisi; Zhou, Wang; Han, Shuangshuang; Zhang, Luyong; Wang, Tao
Abstract: Pre‐diabetes is characterized by impaired glucose tolerance (IGT) and/or impaired fasting glucose. Impairment of skeletal muscle function is closely associated with the progression of diabetes. However, the entire pathological characteristics and mechanisms of pre‐diabetes in skeletal muscle remain fully unknown. Here, we established a mouse model of pre‐diabetes, in which 6‐week‐old male C57BL6/J mice were fed either normal diet or high‐fat diet (HFD) for 8 or 16 weeks. Both non‐fasting and fasting glucose levels and the results of glucose and insulin tolerance tests showed that mice fed an 8‐week HFD developed pre‐diabetes with IGT; whereas mice fed a 16‐week HFD presented with impaired fasting glucose and impaired glucose tolerance (IFG‐IGT). Mice at both stages of pre‐diabetes displayed decreased numbers of mitochondria in skeletal muscle. Moreover, IFG‐IGT mice exhibited decreased mitochondrial membrane potential and ATP production in skeletal muscle and muscle degeneration characterized by a shift in muscle fibers from predominantly oxidative type I to glycolytic type II. Western blotting and histological analysis confirmed that myoblast differentiation was only inhibited in IFG‐IGT mice. For primary skeletal muscle satellite cells, inhibition of differentiation was observed in palmitic acid‐induced insulin resistance model. Moreover, enhanced myoblast differentiation increased glucose uptake and insulin sensitivity. These findings indicate that pre‐diabetes result in mitochondrial dysfunction and inhibition of myoblast differentiation in skeletal muscle. Therefore, interventions that enhance myoblast differentiation may improve insulin resistance of diabetes at the earlier stage. Abstract : Mitochondrial dysfunction may occur earlier than and result in inhibition of myoblast differentiation in a mouse model of pre‐diabetes. Mitochondrial dysfunction in skeletal muscle may contribute to the progression of pre‐diabetes.